Theory of Reflective Modernization as a support for reading Sports and Leisure Public Policies - Temístocles Damasceno Silva; Neidiana Braga da Silva Souza; Rui Proença Garcia; Juliano de Souza (Universidade Salgado de Oliveira, 2021)
The text aims to present some of the potential analytical contributions that Ulrich Beck's theory of reflexive modernization offers to carry out the reading of public policies on sport and leisure in Brazil. Along this path, the emergence of a cosmopolitan realpolitik and meta-games of powers that are increasingly active and decisive on a global scale is considered in order to suggest an analytical design that not only seeks to overcome the borders of the Nation-State but also invests in reflective dimensions of the different actors involved in global political making. With regard to methodological aspects, this is a theoretical article that presents a critical perspective and new hypothetical elements for investigations in the field of sports and leisure policies. For that, we started from the literature and used documents and statistical data as empirical sources for the inferences of the presented assumptions. In this logic, it was possible to show that the sports and leisure policy in Brazil has historically gone through a process of structural reorganization combined with a process of radicalization of modernity in the expansion of the participation of the third sector in the promotion of actions in this area, which caused reflexivity among the actors entangled in this process. Finally, when considering the new dynamics of public sports policy in Brazil, it appears that the theory of reflexive modernization presents itself as a significant theoretical contribution to understanding the current reality.